ยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี : กรณีศึกษาบ้านนาผาแก้ว เมืองมะหาไช แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว - พิศทะยาพอน, สมพร (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
ยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี : กรณีศึกษาบ้านนาผาแก้ว เมืองมะหาไช แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว STRATEGY TO DEVELOP MULTILATERAL PARTICIPATION IN MANAGEMENT OF THE PRODUCTION FOREST : A CASE STUDY IN PHA KAEW VILLAGE, MAHAZAI DISTRICT, KHAMMOUANE PROVINCE, LAO PEOPLE DEMOCRATIC REPUBLIC บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาสภาพปัญหา ความต้องการและแนวทางการจัดการป่าผลิต 2) สร้างยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี 3) ประเมินยุทธศาสตร์การพัฒนาจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคีสำหรับบ้านนาผาแก้ว เมืองมะหาไซ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว และ 4) ปรับปรุงและเผยแพร่ยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี กลุ่มเป้าหมายจำนวน 61 คน เลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์แบบมีโครงสร้าง และแบบสอบถามชนิดมาตราส่วนประมาณค่า สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. สภาพปัญหาป่าผลิตถูกทำลายไปจำนวนมาก ความอุดมสมบูรณ์ของป่าผลิตลดลง สัตว์ป่ามีจำนวนลดน้อยลง ชีวนานาพันธุ์ลดลง ขาดการปลูกต้นไม้ทดแทน ประชาชนขาดความรู้ ความเข้าใจในกฎ ระเบียบข้อบังคับของป่าผลิต คณะกรรมการคุ้มครองป่าที่แต่งตั้งขึ้นมีบทบาทหน้าที่รับผิดชอบไม่ชัดเจนในการปฏิบัติงานทั้งภาครัฐและประชาชน กรรมการชุดนี้ไม่มีเอกชนเข้าร่วม ความต้องการในการจัดการป่าผลิต พบว่า ให้ประชาชนในชุมชนรู้จักการใช้ทรัพยากรป่าผลิตอย่างคุ้มค่า ต้องการให้มีการฟื้นฟูและพัฒนาป่าผลิต ต้องการส่งเสริมการสร้างเครือข่ายในการอนุรักษ์ป่าผลิต และต้องการให้ภาครัฐ เอกชน และประชาชนมีส่วนร่วมในการบริหารจัดการป่าผลิต และแนวทางการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี พบว่า มีข้อเสนอดังนี้: จัดกิจกรรมปลูกจิตสำนึกให้คนในชุมชนในการใช้ทรัพยากรจากป่าผลิตอย่างคุ้มค่า จัดกิจกรรมรณรงค์ฟื้นฟูและพัฒนาป่าผลิต จัดกิจกรรมส่งเสริมการสร้างเครือข่ายในการอนุรักษ์ป่าผลิต และจัดกิจกรรมให้ภาครัฐ เอาชน และประชาชนเข้าถึงการมีส่วนร่วมในการบริหารจัดการป่าผลิต 2. ยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคีที่สร้างขึ้นร่วมกัน ประกอบด้วย การกำหนดวิสัยทัศน์ การกำหนดภารกิจ การกำหนดเป้าประสงค์ (Goal) การกำหนดวัตถุประสงค์ การกำหนดตัวชี้วัด และการกำหนดยุทธศาสตร์ ยุทธศาสตร์ที่กำหนดขึ้นคือ ยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคี ประกอบด้วย 4 โครงการคือ 1) โครงการฟื้นฟูป่าผลิต 2) โครงการจัดสรรพื้นที่รับผิดชอบในการจัดการป่าผลิตแบบมีส่วนร่วม 3) โครงการเพาะพันธุ์กล้าไม้ และ 4) โครงการเสริมสร้างศักยภาพของประชาชนและชุมชนท้องถิ่นในการจัดการป่าผลิตแบบมีส่วนร่วม 3. ผลการประเมินยุทธศาสตร์การพัฒนาการจัดการป่าผลิตแบบมีส่วนร่วมของพหุภาคีในบ้านนาผาแก้ว เมืองมะหาไซ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาวที่พัฒนาขึ้นพบว่าโดยรวมอยู่ในระดับมาก ABSTRACT The purposes of this study were: 1) to investigate the problem state, needs and guidelines of production forest management, 2) to create a strategy to develop multilateral participation in management of the production forest, 3) to assess the strategy to develop multilateral participation in management of the production forest for the Na Pha Daew village, Mahazai district, Khammaouane province, Lao People’s Democratic Republic, and 4) to revise and disseminate the strategy to develop multilateral participation in management of the production forest. The target group was of 61 people selected by purposive sampling. The instruments used in study were a structured interview and a rating scale questionnaire. Statistics used in data analysis were frequency, percentage, mean and standard deviation. The findings were as the following. 1. The problem states disclosed that a lot of production forest has been destroyed; richness of it has been reduced; a number of wild lives and bio-species have ben decreased; there has been a lack of reforestation; people lacked knowledge and understanding of rules and regulations of production forest. The appointed forest protection committee members from both the public sector and people themselves had unclear role and responsibility in performance; and they did not include any member from the private sector. The needs of production forest management revealed that people in the community needed to know how to use forest product resources effectively; needed to have the production forest revived and developed; needed the promotion of creating a network for conservation of production forest; and needed of participation in management of the production forest from the public and private sectors and people themselves. The guidelines of multilateral participation in management of the production forest disclosed that the activity to cultivate awareness in the community people should be arranged for them to know how to use resources from the production forest effectively and that the arrangements of activities in launching a program for reviving and developing the production forest, in promoting the creation of a network in conservation of it, and in participating in management of the production forest by public and private sectors and people themselves are required. 2. The strategy to develop multilateral participation in management of the production forest created by people participation consists of vision, mission, goal, objectives, key performance indicators and strategy. The strategy is of developing the multilateral participation in management of the production forest comprising 4 projects: 1) reviving the production forest; 2) allocating the responsible area in participatory management of the production forest; 3) breeding and seedling for planting; and 4) enhancing the capability of people and local community in participatory management of production forest. 3. The result of assessing the developed strategy to develop multilateral participation in management of the production forest in the Na Pha Kaew village, Mahazai district, Khammouane province, Lao People’s Democratic Republic as a whole was at high level.